Higher education learning outcomes assessment : international perspectives - Coates, Hamish, 1974- (Higher education research and policy, 2014)
"This book provides higher education teachers, leaders and policymakers with insights from research on assessing students' learning outcomes. The book is founded in research, shaped by policy, and designed to be of enduring relevance to practice. Framed by a cycle of continuous quality improvement, it begins by discussing policy contexts and research concepts. Experts discuss institutional, disciplinary, national and international case studies. Perspectives are advanced for reviewing the relevance and feasibility of assessment initiatives. The book explores what stakeholders have done to convert work on learning outcomes into improvements in education"--